Phase 1 study to access safety, tolerability, pharmacokinetics, and pharmacodynamics of kynurenine in healthy volunteers - Mohammad Al‐Mahdi Al‐Karagholi; Jakob Møller Hansen; Dalia Abou‐Kassem; Anna Koldbro Hansted; Kumari Ubhayasekera; Jonas Bergquist; László Vécsei; Inger Jansen‐Olesen; Messoud Ashina (Wiley, 2021)
Abstract The kynurenine pathway (KP) is the main path for tryptophan metabolism, and it represents a multitude of potential sites for drug discovery in neuroscience, including pain, stroke, and epilepsy. L‐kynurenine (LKYN), the first active metabolite in the pathway, emerges to be a prodrug targeting glutamate receptors. The safety, tolerability, pharmacokinetics, and pharmacodynamics of LKYN in humans have not been previously investigated. In an open‐label, single ascending dose study, six participants received an intravenous infusion of 50, 100, and 150 µg/kg LKYN and new six participants received an intravenous infusion of 0.3, 0.5, 1, and 5 mg/kg LKYN. To compare the pharmacological effects between species, we investigated in vivo the vascular effects of LKYN in rats. In humans, LKYN was safe and well‐tolerated at all dose levels examined. After infusion, LKYN plasma concentration increased significantly over time 3.23 ± 1.12 µg/mL (after 50 µg/kg), 4.04 ± 1.1 µg/mL (after 100 µg/kg), and 5.25 ± 1.01 µg/mL (after 150 µg/kg) (p ≤ 0.001). We observed no vascular changes after infusion compared with baseline. In rats, LKYN had no effect on HR and MAP and caused no dilation of dural and pial arteries. This first‐in‐human study of LKYN showed that LKYN was safe and well‐tolerated after intravenous infusion up to 5 mg/kg over 20 minutes. The lack of change in LKYN metabolites in plasma suggests a relatively slow metabolism of LKYN and no or little feed‐back effect of LKYN on its synthesis. The therapeutic potential of LKYN in stroke and epilepsy should be explored in future studies in humans.